Características reprodutivas da paca fêmea (Agouti paca) criada em cativeiro - GUIMARÃES, Diva Anelie de Araújo (Instituto Nacional de Pesquisas da Amazônia, 2012)
The objective of this paper was to study the reproductive biology of the Agouti paca raised in captivity. It was observed that the estrous cycle average was 32.5 + 3.7 days, gestation length 148.6 + 4.8 days, parturition interval 224.5 + 52.2 days, and the first post-partum 25.6 + 8.8 days. It was also observed that 55.5% of the females presented two parturitions per year with one young per parturition, of which 44.7% were females and 55.3% were males. The birth weight was 605.9 + 87.8 g for females and 736.7 + 108.4 g for males (P<0.05). Puberty in females occurred between 8 to 12 months; for this, however, more detailed investigations are necessary.